2023
DOI: 10.3390/en16020779
|View full text |Cite
|
Sign up to set email alerts
|

Energy Distribution Diagram Used for Cost-Effective Battery Sizing of Electric Trucks

Abstract: One possible step for reducing humans’ use of fossil fuel due to transport tasks is to replace diesel trucks with battery electric ones. This paper introduces the energy distribution diagram, which makes it easy to visualise the trucks’ daily energy consumption over their full service life. The energy distribution is used to investigate which driving patterns are suitable for cost-effective battery electric trucks when compared to commercial diesel trucks. It is shown that the battery capacity that results in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 14 publications
0
22
0
Order By: Relevance
“…Currently, the oil depletion time is less than 30 years [1], the Earth's climate system has likely been affected [2], and several adverse health impacts have emerged, as expressed in the literature [3]. Battery electric trucks seem to be a part of the solution since several studies have concluded that battery electric trucks could become a cost-efficient, fossil-free alternative to today's commercial diesel trucks [4][5][6][7][8]. The literature shows that the cost-effectiveness of battery electric trucks is sensitive to driving patterns [4], whereas relatively uniform driving patterns are most suitable for electrification [4,9].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, the oil depletion time is less than 30 years [1], the Earth's climate system has likely been affected [2], and several adverse health impacts have emerged, as expressed in the literature [3]. Battery electric trucks seem to be a part of the solution since several studies have concluded that battery electric trucks could become a cost-efficient, fossil-free alternative to today's commercial diesel trucks [4][5][6][7][8]. The literature shows that the cost-effectiveness of battery electric trucks is sensitive to driving patterns [4], whereas relatively uniform driving patterns are most suitable for electrification [4,9].…”
Section: Introductionmentioning
confidence: 99%
“…Battery electric trucks seem to be a part of the solution since several studies have concluded that battery electric trucks could become a cost-efficient, fossil-free alternative to today's commercial diesel trucks [4][5][6][7][8]. The literature shows that the cost-effectiveness of battery electric trucks is sensitive to driving patterns [4], whereas relatively uniform driving patterns are most suitable for electrification [4,9]. Hydrogen trucks could also be a part of the solution; however, previous studies mostly favour battery electric trucks [10,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past few years, automotive manufacturers have prioritized the lightweight construction of electric delivery truck frames and the design of battery compartments (Zhang et al 2020;Zhou et al 2022). Looking ahead, as incentive programs, policy facilitation, and technological advancements continue to evolve, the future of electric delivery trucks appears promising, with a positive outlook (Hovi et al 2019;Nykvist and Olsson 2021;Karlsson and Grauers 2023;Ramirez Ibarra and Saphores 2023).…”
Section: Introductionmentioning
confidence: 99%
“…However, the number of registrations of heavy electric trucks is still very low. Many studies have been published on the technical and economic aspects of electric trucks [3][4][5][6], but there is a lack of information on user acceptance. This paper examines the perception of e-trucks in the German market to provide insight into the acceptance of this technology.…”
Section: Introductionmentioning
confidence: 99%